Adolescent Perceptions and Experiences of the Hijab: a Qualitative Canadian Study - Funnell-Kononuk, Emma (Journal of childhood and religion, 2017)
In this study, we useda phenomenological method to explore of adolescent experiences of hijabsin a medium-sized Canadiancity. Using a focus group for data collection, six Muslim adolescents (two hijabi girls, two non-hijabi girls,and two boys) aged 12-15 shared their experiences regarding hijabs in a public school environment, and describedoccurrencesinvolvingpeers, teachers,and expectations. Findings suggestedthat adolescent girls consider many factors when choosing whether or not to wear a hijab, includingpracticalityand anindividual sense of style,along with more internal reasons. Both girls and boys saw wearing ahijab as a way of representing Islam, and discussion about the hijab led theminto a broaderdiscussion aboutbeing Muslimand their related concern that Islam is often misunderstood. This paper offers insight into adolescent perceptions of wearing a hijab and being Muslim in a largely non-Muslim community.